Toxicity, phytochemical content and antioxidant activity assessment studies for a standardized ethanolic fraction of palm oil leaf extract - Ibraheem, Zaid O.; Sattar, Munavvar A.; Abdullah, Nor A.; Hassaan, Rathore; Johns, Edward J. (Pharmacognosy Communications)
Palm oil is one of the main contributors to vegetable oil industry. Its fronds are always discarded as waste products. Nowadays, there are some studies focused the light on the biomedical importance of palm oil leaf extract as a comestible health product. In this study, ethanolic fraction of the extract was used. Its antioxidant activity was investigated by using reducing power assay, free radical scavenging activity, hydrogen peroxide inhibition assay and antilipid peroxidation assay. The polyphenols and flavnoids contents were determined. Using Folin Ciocaleau and Sakanaka tests. LD50 was determined using OCED protocol (Up and down procedure). The subchronic toxicity was assessed by feeding the extract in 3 different doses 0.5, 1 and 2 g/kg/day for 24 days. At the end gross and necroscopical examinations were performed. Results showed that POLE possesses an antioxidant activity and its safety limit is high. Overall, POLE can be used as a comestible health product to protect organs against injury.
Keywords: Antioxidant; polyphenols; peroxidation; palm oil and free radicals